SYNTACTIC VALENCY AND COMBINABILITY PATTERNS OF ADVERBS - Kutlimuratova, A. (Eurasian Journal of Academic Research, 2023)
Every word is characterized by its semantic and syntactic valencies potentially inherent in it, which in syntagmatics become the actualization of these potentials, i.e. semantic (or lexical) and syntactic combinabilities.